Peningkatan Keaktifan Belajar Menulis Teks Deskriptif melalui Model Cooperative Learning Tipe Snowball Throwing bagi Siswa MTs Negeri 8 Kebumen - Arimurti, Surinta (Discovery, 2024)
This research aimed to find out how much student activity and learning outcomes had increased after implementing the Snowball Throwing type Cooperative Learning model on the material for writing descriptive texts in English subjects at MTs Negeri 8 Kebumen. This research was a type of Classroom Action Research (PTK). The research subjects were 30 students in class VII G of MTs Negeri 8 Kebumen. The sample selection technique used purposive sampling technique. Data collection techniques in this research used observation sheets and tests. Data analysis was carried out using descriptive analysis. The research results showed that the implementation of the snowball throwing type of Cooperative Learning model could be seen as follows: 1) This model was proven to increase student activity. It could be seen from the increase in each cycle, cycle I was 63% and cycle II was 86.7%. 2) Implementation of learning using this model had been proven to improve student learning outcomes. It could be seen in cycle I the number of students who completed their studies was 63%, and cycle II was 87%. Actions were said to be successful if there was an increase in learning outcomes from cycle I to cycle II and the percentage of students who achieved the KKM (complete) score had reached at least 80%.